Long-Term Care: Choices for Thailand as a Middle-Income Country - and Supasit Pannarunothai, Nalinee Chuakhamfoo (Journal of Community Development Research (Humanities and Social Sciences); Vol 9 No 1 (2559): January - April 2016, 2016)
Background: The demand for long-term care services in Thailand is rising rapidly because of an increasing of functional limitation of the aging population. Meanwhile, the preparation and arrangement of public long-term care system in Thailand are not available to meet the needs of these people. Aim: The aim of this study was to review the literature on the definition of long-term care, analyze the long-term care system that affect the quality of life, operation of care providers, and the policy management in selected countries to be the lesson learnt for Thailand. Method: The research strategy covered computerized journal databases: EBSCO, PsychInfo, Routledge, BioMed Central, Blackwell, Elsevier Science, and Palliative Medicine database from 1996 to 2015. The selected articles included quantitative and qualitative studies related to long-term care system policies and benefits. Results: Long-term care is the system to support dependency groups such as elderly, disable, or people with mal-cognitive function. It has formal and informal care which can enhancing well-being in biological, psychological, and social factors of individuals. Many countries has its own management depends on the context. Thailand also has the unique context to develop long-term care system beginning from health care aspect and expand to social care aspect. Conclusion: Long-term care is a multi-dimensional system. Many countries invest in health care, social, psychological, and financial part to complete the system. As Thailand is one of many countries that try to setup the appropriate long-term care system but not only the holistic long-term care system that Thailand has to concern, the sustainability aspect for running the system properly should be the key factor for policy makers to consider as well.   Keywords:  Long-Term Care Policy, Elderly, Adult Aging, Aging Population, Quality of Life, Consumer Needs, Services,  Benefit Package, Providers, Management.
Keywords: Long-Term Care Policy, Elderly, Adult Aging, Aging Population, Quality of Life, Consumer Needs, Services, Benefit Package, Providers, Management